Archetype, attachment, analysis : Jungian psychology and the emergent mind - Knox, Jean, 1948- (Brunner-Routledge, 2003)
Archetype, Attachment, Analysis is a well-researched presentation of new material that offers a revision and reinterpretation of Jung's archetypal hypothesis. The author's ground breaking new exploration of expanding knowledge from other disciplines such as cognitive science and developmental psychology, and attachment theory and research evidence sheds important new light on Jungian theory and practice. Using information gathered through laboratory investigations and natural observational studies Jean Knox brings the notion of archetypes up to date and considers the implications.